Adsorption of Cobalt(II) Ions from Aqueous Solution onto Activated Carbon Prepared from Hazelnut Shells - Erhan Demirbaş (Adsorption Science & Technology)
Activated carbon prepared from hazelnut shells was used to remove Co(II) from aqueous solution by adsorption. Batch-mode adsorption experiments were carried out varying parameters such as the initial metal ion concentration (13.30–45.55 mg/l), agitation speed (50–200 rpm), pH (2–8), temperature (293–323 K) and particle size (0.80–1.60 mm). The kinetics of the adsorption of Co(II) followed the pseudo-second-order equation, being pH-dependent since the removal rate increased with the pH value of the aqueous solution. The adsorption equilibrium data obeyed the Langmuir isotherm. The adsorption capacity (Q 0 ) calculated from the Langmuir isotherm was 13.88 mg Co(II)/g carbon at 303 K employing a pH value of 6 and a particle size of 1.00–1.20 mm. The thermodynamic parameters evaluated for the carbon revealed that the adsorption of Co(II) was endothermic in nature.